Pharmacological inhibition of PPARγ increases osteoblastogenesis and bone mass in male C57BL/6 mice. (15th February 2013) - Duque, Gustavo; Li, Wei; Vidal, Christopher; Bermeo, Sandra; Rivas, Daniel; Henderson, Janet
Abstract: Infiltration of bone marrow with fat is a prevalent feature in people with age‐related bone loss and osteoporosis, which correlates inversely with bone formation and positively with high expression levels of peroxisomal proliferator‐activated receptor gamma (PPARγ). Inhibition of PPARγ thus represents a potential therapeutic approach for age‐related bone loss. In this study, we examined the effect of PPARγ inhibition on bone in skeletally mature C57BL/6 male mice. Nine‐month‐old mice were treated with a PPARγ antagonist, bisphenol‐A‐diglycidyl ether (BADGE), alone or in combination with active vitamin D (1, 25[OH]2 D3 ) for 6 weeks. Micro‐computed tomography and bone histomorphometry indicated that mice treated with either BADGE or BADGE + 1, 25(OH)2 D3 had significantly increased bone volume and improved bone quality compared with vehicle‐treated mice. This phenotype occurred in the absence of alterations in osteoclast number. Furthermore, the BADGE + 1, 25(OH)2 D3 ‐treated mice exhibited higher levels of unmineralized osteoid. All of the treated groups showed a significant increase in circulating levels of bone formation markers without changes in bone resorption markers, while blood glucose, parathyroid hormone, and Ca + remained normal. Furthermore, treatment with BADGE induced higher levels of expression of vitamin D receptor within the bone marrow. Overall, treated mice showed higher levels of osteoblastogenesis and bone formation concomitant with decreased marrow adiposity and ex vivo adipogenesis. Taken together, these observations demonstrate that pharmacological inhibition of PPARγ may represent an effective anabolic therapy for osteoporosis in the near future. © 2013 American Society for Bone and Mineral Research.